Comparison of treatment regimens for unresectable stage III epidermal growth factor receptor (EGFR) mutant non-small cell lung cancer - Xin Dai; Qian Xu; Lei Sheng; Xue Zhang; Miao Huang; Song Li; Kai Huang; Jiahui Chu; Jian Wang; Jisheng Li; Yanguo Liu; Jianyuan Zhou; et al. (Chinese Medical Journal, 2025)
Abstract. Background:. Durvalumab after chemoradiotherapy (CRT) failed to bring survival benefits to patients with epidermal growth factor receptor (EGFR) mutations in PACIFIC study (evaluating durvalumab in patients with stage III, unresectable NSCLC who did not have disease progression after concurrent chemoradiotherapy). We aimed to explore whether locally advanced inoperable patients with EGFR mutations benefit from tyrosine kinase inhibitors (TKIs) and the optimal treatment regimen. Methods:. We searched the PubMed, Embase, the Cochrane Central Register of Controlled Trials, and ClinicalTrials.gov databases from inception to December 31, 2022 and performed a meta-analysis based on a Bayesian framework, with progression-free survival (PFS) and overall survival (OS) as the primary endpoints. Results:. A total of 1156 patients were identified in 16 studies that included 6 treatment measures, including CRT, CRT followed by durvalumab (CRT-Durva), TKI monotherapy, radiotherapy combined with TKI (RT-TKI), CRT combined with TKI (CRT-TKI), and TKI combined with durvalumab (TKI-Durva). The PFS of patients treated with TKI-containing regimens was significantly longer than that of patients treated with TKI-free regimens (hazard ratio [HR] = 0.37, 95% confidence interval [CI], 0.20–0.66). The PFS of TKI monotherapy was significantly longer than that of CRT (HR = 0.66, 95% CI, 0.50–0.87) but shorter than RT-TKI (HR = 1.78, 95% CI, 1.17–2.67). Furthermore, the PFS of RT-TKI or CRT-TKI were both significantly longer than that of CRT or CRT-Durva. RT-TKI ranked first in the Bayesian ranking, with the longest OS (60.8 months, 95% CI = 37.2–84.3 months) and the longest PFS (21.5 months, 95% CI, 15.4–27.5 months) in integrated analysis. Conclusions:. For unresectable stage III EGFR mutant NSCLC, RT and TKI are both essential. Based on the current evidence, RT-TKI brings a superior survival advantage, while CRT-TKI needs further estimation. Large randomized clinical trials are urgently needed to explore the appropriate application sequences of TKI, radiotherapy, and chemotherapy. Registration:. PROSPERO; https://www.crd.york.ac.uk/PROSPERO/; No. CRD42022298490.